Tracing the Development of Islamic Economic Thought in the Abbasid Era: The Legacy of Umar bin Khattab - Mujib, Ahmad; Aziz, Abdul; Madrah, Muna Yastuti; Wahid, Zawawi Abdul (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2024)
The expansion of Islamic territories during the time of Umar ibn Khattab led to increasingly complex problems, especially in the economic field. During this period, Umar ibn Khattab introduced remarkable, though sometimes controversial, policies. These policies and ideas were extensively studied by scholars during the Abbasid Caliphate and became the foundation for the development of Islamic economic thought. This article reveals several areas where the study of Islamic economics made significant progress. It is based on a literature review using primary sources such as the books of Ali Muhammad As-Shalabi and Jaribah bin Ahmad Al-Haritsi, utilizing a historical approach. The research results show a strong scholarly tradition, accompanied by the documentation of many accounts from Umar ibn Khattab, especially in the domains of kharaj, ‘usyr, jizyah, and the institution of al-hisbah. This demonstrates that Umar ibn Khattab laid the intellectual foundations in the fields of economics and Islamic jurisprudence. During that time, scholarly studies on economics continued to develop. The books discussed by scholars of that era covered various aspects of Islamic economic thought, all of which were closely related to the government